Demographic Characteristics of Glial Fibrillary Acidic Protein (GFAP) in Patients with Multiple Sclerosis, Karbala Governorate, Iraq - Al-Tamimi, Huda Adnan; Al-Ghanmi, Yasmine Khudair (American Journal of Biology and Natural Sciences, 2025)
(MS) is a chronic autoimmune disease that results in damage to the myelin sheath covering nerve cells and the central nervous system.The (GFAP) is uniquely found in astrocytes in the central nervous system and non-myelinating Schwann cells in the peripheral nervous system,and it is assumed to be a biomarker for astrocytic damage in multiple sclerosis patients. The aim of this study was to investigate the demographic characteristics of serum levels of (GFAP) among a group of Iraqi patients with (MS) and a group of healthy individuals.The study included 90 samples,(45) patients with multiple sclerosis in stages (1, 2, 3), and (45) healthy individuals and GFAP levels in serum were studied using the ELISA immunoassay.The results showed that despite the slightly increased levels of GFAP in the patient group with age, the difference was not statistically significant (P=0.408). The average GFAP levels in the male patient group were higher than in females with a value of (P=0.061), which is slightly above the level of statistical significance (P=0.05). There is a statistically significant increase in GFAP levels, and the data indicated that GFAP levels gradually increase with the duration of the disease, suggesting an exacerbation of multiple sclerosis over time with a value of (P=0.004).Conclusion: These results support the idea that the increase in GFAP is a condition of the disease rather than age in these samples, and that BMI category does not significantly affect GFAP concentrations in the patient group. This supports the idea that the increase in GFAP levels is independent of body weight in this study. Regarding gender, although the difference is not statistically significant, it indicates a trend towards increased GFAP, suggesting that a larger sample size may confirm statistical significance. GFAP may be a biomarker for disease progression, especially in chronic or long-term cases.